Platelet Aggregation, β-Thromboglobulin and Platelet Factor 4 in Diabetes Mellitus and in Patients with Vasculopathy - Fritschi, J; Christe, M; Lämmle, B; Marbet, G A; Berger, W; Duckert, F (Thrombosis and Haemostasis, 1984)
We have studied 155 subjects, 48 normals, 36 diabetics without complications, 44 with complications and 27 patients with macroangiopathy. β-Thromboglobulin (β-TG) and platelet factor 4 (PF4) are elevated in the patients groups. There is no correlation between the plasma levels of β-TG and the stages of either retinopathy or macroangiopathy or nephropathy. The difference is more marked between normals and diabetics with neuropathy (p = 0.026). The aggregation response to ADP and platelet activating factor (PAF) is enhanced at lower stimulator concentration. Using the β-TG, PF4 and aggregation values the discriminant analysis allows a distinction of several subgroups especially with nephropathy and neuropathy (Table 6).
Keywords: Diabetes mellitus; Nephropathy; Platelet aggregation; βThromboglobulin; Platelet factor 4